2021
DOI: 10.22541/au.161360058.82373663/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Heterogeneous Hydrogen Bond Environment in Hydrophobic Deep Eutectic Solvents

Abstract: Hydrophobic deep eutectic solvents (DESs) have emerged as excellent extractants. Their performance depends on the heterogeneous hydrogen bond environment formed by multiple hydrogen bond donors and acceptors. An understanding of this heterogeneous hydrogen bond environment can be used to develop principles for designing high-performance DESs for extraction and other separation applications. We investigate the structure and dynamics of hydrogen bonds in eight hydrophobic DESs formed by decanoic acid, menthol, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They are also highly hygroscopic, and the water content needs to be quantified as it significantly affects their physical properties. On the other hand, the so-called hydrophobic DESs have only recently been reported. ,, They typically consist of long-chain fatty acids and quaternary ammonium salts with long alkyl chains or small organic molecules (menthol, thymol, ibuprofen, organic acids) and have been shown to be promising solvents for the extraction of natural compounds and metals from aqueous solutions. They have higher viscosity and lower conductivity than hydrophilic DESs but we have recently demonstrated their use as solvents in electrochemistry . Their properties are less studied but their formation, vapor pressure, density, and viscosity have been characterized and discussed using theoretical fluid models and molecular dynamics simulations. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…They are also highly hygroscopic, and the water content needs to be quantified as it significantly affects their physical properties. On the other hand, the so-called hydrophobic DESs have only recently been reported. ,, They typically consist of long-chain fatty acids and quaternary ammonium salts with long alkyl chains or small organic molecules (menthol, thymol, ibuprofen, organic acids) and have been shown to be promising solvents for the extraction of natural compounds and metals from aqueous solutions. They have higher viscosity and lower conductivity than hydrophilic DESs but we have recently demonstrated their use as solvents in electrochemistry . Their properties are less studied but their formation, vapor pressure, density, and viscosity have been characterized and discussed using theoretical fluid models and molecular dynamics simulations. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…However, it is not trivial to determine which HB properties could be used. Our previous work [52] found that the non-ionic DESs can be broadly classified into three groups based on the ratio of intra-and inter-component HB numbers. Such observations inspire us to explore the possibility of developing machine learning models using HB-based descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine 8 has also been reported as a promising candidate in the pharmaceutical industry. We have investigated the bulk phase properties of these eight DES systems in our previous work 47 . The work here is a continuous effort to advance our understanding of the interfacial behavior of these eight hydrophobic DESs.…”
Section: Introductionmentioning
confidence: 99%